2022
DOI: 10.1039/d2lc00114d
|View full text |Cite
|
Sign up to set email alerts
|

Engineering cell–substrate interactions on porous membranes for microphysiological systems

Abstract: Microphysiological systems are now widely used to recapitulate physiological and pathological microenvironments in order to study and understand a variety of cellular processes as well as drug delivery and stem...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 77 publications
(223 reference statements)
0
12
0
Order By: Relevance
“…These parameters affect cell adhesion. It is known that smoother surfaces have less adhesiveness than materials with a rough surface [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters affect cell adhesion. It is known that smoother surfaces have less adhesiveness than materials with a rough surface [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, most cells with larger micropore sizes (3.0–8.0 µm in diameter) showed a more spherical cell shape with fewer filopodia and lamellipodia, indicating a decrease in the adhesiveness of the material. Zahra Allahyari et al [ 62 ] confirmed in their review that small pores at the nanoscale promote the strongest cell-substrate interactions, while the largest pores at the micron scale prevent these interactions. It is also known that smooth surfaces have weaker adhesion than the surface of a material with moderate porosity.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies demonstrated the correlation between surface features and the behavior of cells [ 33 , 34 , 35 ]. A recent review provides insight into the importance of membrane pores in controlling cellular responses [ 36 ]. Here, SEM and histological analyses revealed a porous structure that seems to favor the biological activities of both HGF and HOB, demonstrated by the higher expression of functional genes, above all the genes related to ECM components.…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesions, generally located at the cell periphery, anchor ECs to underlying substrates. Their numbers directly correlate with the strength of cell‐matrix interactions, particularly on stiff substrates 45–47 . Relative to nonporous substrates, the disrupted surface geometry of porous glass membranes decreased cell‐substrate contact area, ultimately reducing cell‐matrix interactions and focal adhesion formation.…”
Section: Discussionmentioning
confidence: 99%